2020
DOI: 10.1123/jsr.2018-0207
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Noncontact Injuries and the Acute—Chronic Workload Ratio in Elite-Level Athletes: A Critically Appraised Topic

Abstract: Clinical Scenario: Workload monitoring and management of an athlete is viewed by many as an essential training component to determine if an athlete is adapting to a training program and to minimize injury risk. Although training workload may be measured a variety of different ways, session rate of perceived exertion (sRPE) is often used in the literature due to its clinical ease. In recent years, sports scientists have been investigating sRPE as a measure of internal workload and its relationship to injury in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The heterogeneity of training intensities and durations suggests that athletes will either undertrain, over-train, or train at an optimal workload relative to their training intensities during the pre-lockdown period. Based on trends in the literature (Gabbett, 2010;Blanch and Gabbett, 2016;Bowen et al, 2020;Myers et al, 2020), we hypothesize that the incidence of injury will be primarily bimodal, particularly evident in the athletes that over-and undertrain relative to pre-lockdown intensities. The undertraining cohort will suffer injuries (oblique, groin, and hamstring strains) manifesting from the lack of progression in chronic workload.…”
Section: Current and Emerging Focal Point: Monitoring The Return-to-play Status Of Athletes Following Covid-19mentioning
confidence: 99%
“…The heterogeneity of training intensities and durations suggests that athletes will either undertrain, over-train, or train at an optimal workload relative to their training intensities during the pre-lockdown period. Based on trends in the literature (Gabbett, 2010;Blanch and Gabbett, 2016;Bowen et al, 2020;Myers et al, 2020), we hypothesize that the incidence of injury will be primarily bimodal, particularly evident in the athletes that over-and undertrain relative to pre-lockdown intensities. The undertraining cohort will suffer injuries (oblique, groin, and hamstring strains) manifesting from the lack of progression in chronic workload.…”
Section: Current and Emerging Focal Point: Monitoring The Return-to-play Status Of Athletes Following Covid-19mentioning
confidence: 99%
“…Supraphysiologic overloading also appears to have a temporal component in this population. 4 , 6 , 29 Our data further suggested that the temporal component differs between the sexes and begins to diverge early, at the more exhaustive events (eg, the Warrior Competition, 12-mile ruck). We speculate that the acute effort needed to complete these events (ie, load placed upon the tissues), particularly for female cadets, was far greater than the average (ie, chronic) load placed on tissues over the previous weeks.…”
Section: Discussionmentioning
confidence: 52%
“…In 2016, the International Olympic Committee (IOC) published a consensus statement (Soligard et al, 2016) that suggests the use of the ACWR approach for injury prevention. In addition, Myers et al (2020) reported level A evidence in support of the sRPE ACWR as an effective tool to prevent non-contact injuries in elite athletes. Despite evidence in favor of the ACWR approach, different authors have raised substantial criticism (Impellizzeri et al, 2020a,b;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%